1986
DOI: 10.1128/mcb.6.5.1545
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of chicken embryo fibroblasts and tumor induction by the middle T antigen of polyomavirus carried in an avian retroviral vector.

Abstract: The middle T antigen of polyomavirus transformed primary chicken embryo fibroblasts when expressed from a replication-competent avian retrovirus. This in vitro-constructed retrovirus, SRMT1, is a variant of Rous sarcoma virus that encodes the middle T antigen in place of v-src. Inoculation of SRMT1 into 1-week-old chickens rapidly induced hemangiomas and hemanglosarcomas. As shown with mammalian cells infected with polyomavirus, polyomavirus middle T antigen appears to be associated with p6(c-SFc in chicken ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…Infection of CEF with a retrovirus interferes with infection by a second virus unless the two viruses have different subgroup specificities (14). For the double-infection experiments, we therefore produced virus stocks of subgroup A or B by transfecting with the appropriate version of pSR-REP (27). Soft agar colony formation was performed as described previously (33).…”
Section: Methodsmentioning
confidence: 99%
“…Infection of CEF with a retrovirus interferes with infection by a second virus unless the two viruses have different subgroup specificities (14). For the double-infection experiments, we therefore produced virus stocks of subgroup A or B by transfecting with the appropriate version of pSR-REP (27). Soft agar colony formation was performed as described previously (33).…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, the foreign DNA sequences were inserted in place of the coding region for src, which is dispensable for virus replication (7,11,15). Other vectors, based on the replication-competent avian spleen necrosis virus, have been constructed and enable the introduction of foreign sequences downstream from the coding sequences for env (8).…”
mentioning
confidence: 99%
“…Many studies have shown that PyMT can transform epithelial and endothelial cells leading to hemangiosarcomas, mammary tumors, and other neoplasms of epithelial origin (17,20,22,38). However, leukemia or lymphoma are not a reported consequence of PyMT expression in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Polyoma middle T (PyMT) is a membrane-associated oncoprotein that can transform endothelial cells and induce hemangiomas in chickens (20) and in mice (21,22). Using SCL-TVA mice and recombinant RCAS/PyMT viruses, we were able to efficiently deliver PyMT to vascular endothelial progenitors and found that the infected mice rapidly succumbed to a fatal hemorrhagic disease due to hemangioma formation.…”
mentioning
confidence: 99%